Effect of Velocity and Type of Cooling Fluid on Peltier Heat Transfer for Car Cabin Cooling Applications - Eko Yudiyanto; Ridho Surya Setiabudi; Agus Hardjito; Satworo Adiwidodo; Bayu Pranoto (Widyagama University of Malang, 2022)
This research used the Peltier element as a car cabin cooler. This research aimed to compare the results of the lowest temperature produced by the Peltier element on the hot side. The design of this monitoring tool consists of LM35 as a temperature sensor and an electric velocity sensor to measure the velocity of the cooling fluid. Arduino Uno Microcontroller to control the system before being displayed to the LCD. The type of research used in this research is experimental research. In this study, variations in fluid flow velocity and type of cooling fluid were carried out. The fluid used is a mixture of water and water coolant with a ratio of 50%:50%. The results showed that the circulation of fluid cooling influences the temperature on the hot side of the Peltier. In cooling using water fluid, when the water pump rotates 4.5 liters/second, the temperature on the hot side of the Peltier is 36ᵒC. At the time of rotation of 13 liters/second, the temperature on the hot side of the Peltier is 32ᵒC. The difference between cooling using water fluid, water coolant, or a mixture of water and water coolant greatly affects the temperature produced on the cold side of the Peltier. In cooling using water, the lowest temperature produced reaches 8ᵒC. When the cooling using a fluid coolant, the lowest temperature reaches 6ᵒC. While cooling using a mixture of water and coolant, the lowest temperature reaches 3ᵒC. So it can be concluded that cooling using a mixture of water and water coolant is very effective compared to other fluid coolers.